Study on the economic potential of far edge computing in the future smart Internet of Things (Publications Office of the European Union, 2023)
This study details both the economic opportunities and environmental impacts of a paradigm shift in the domain of the Internet of Things (IoT) towards computing at the Edge. The study's objectives are aligned with that of the targets of the Digital Decade and contribute to the objectives of the Horizon Europe strategic plan for the development of technologies, standards and experimentation for users that will support Edge Computing for the future smart IoT. This study provides a thorough analysis of the competitive positioning of the EU on Professional IoT (Automotive electronics, factory automation, energy management IoT, security IoT, connected health & care devices, asset trackers for logistics and finally IoT for agriculture), which correspond to major industrial strengths and opportunities for the EU in light of the digital transition. Indeed, since 2021, Professional IoT's global market exceeds the market of consumer IoT, and the EU professional IoT manufacturers are still in a leading position worldwide, with 28% market shares, ahead of China and the USA. Professional IoT markets are also key to ensure the success of the EU green transition, given their role in new renewable energy production, smart grids, and green mobility. In this regard, a successful deployment of the Cloud-to-edge computing continuum is a prerequisite for the establishment of mature smart grids. This study answers the need of clear definition of edge computing and of its impact along the value chain of IoT, generating new business models and challenging the position of established players. In 2021, the ICT sector represented 4% of the total carbon footprint of humanity and its environmental footprint is expected to reach 7% by 2030. Professional IoT alone correspond to one third of this impact. Considering the EU's climate goals and plans (Green Deal), and in line with DG CNECT's priorities, this study provides a detailed environmental impact assessment of the global deployment of professional IoT and how the edge computing trend is affecting this environmental impact. Finally, chips supply plays an increasing role for EU's industrial fabric, and this is particularly reflected while studying the impact of edge computing on IoT. This is why these study's findings are of interest for the guidance of the EU Chips Act implementation. For this study, DECISION designed a segmentation of the types of semiconductors required to perform computing functions (processors and memories), depending on the intensity of computing capabilities they can ensure: thin, medium, or thick. This segmentation enables to easily position the European suppliers in the global semiconductor competition, as overall the EU ecosystem is strong in thin computing semiconductors, and small and reliant on US providers on thick computing semiconductors.
10.2759/05608
Keywords: Graue Literatur; Amtliche Publikation; Internet der Dinge; Datenverarbeitung; Halbleiterindustrie; Betriebliche Wertschöpfung; Internationaler Wettbewerb; Umweltverträglichkeitsprüfung; EU-Forschungspolitik; EU-Staaten; Internet of Things; business model; environmental impact; digital transformation; value chain; competitiveness; new technology; economic consequence; smart technology; automation; industrial policy; Horizon Europe; Horizon Europe